Commonsense statistics for economists and others - Jolliffe, F. R. (London ; Boston : Routledge & Kegan Paul, 1974)
This book was aims to teach the fundamental ideas of statistics in a manner that should not be scorned by the numerate and will be understood by the non-numerate.
Bibliography: p. 173-174.
aia 05/10/17
Loans
Keywords: Statistics